Determinants of leisure time physical activity among elderly with type 2 diabetes mellitus in Petaling District, Selangor, Malaysia - Nedunsaliyan, Sankari (2019)
Globally people are living longer due to medical advancement, better awareness and knowledge towards the importance of healthy lifestyle. Reduction of physical activity commonly linked with increasing age, due poor health and physical tolerance and is associated with comorbidity such as type 2 diabetes mellitus. Type 2 diabetes mellitus accounted as most burdening cause of morbidity among elderly and it is often regarded with reduction in physical activity. This study aimed to determine the factors associated with leisure time physical activity among elderly with T2DM in Petaling district Selangor according to the Socio-ecological model. A cross-sectional study was conducted in 6 health clinics within Petaling District Selangor, using stratified to proportionate size sampling and simple random sampling methods. Data collected through pre-tested and validated questionnaire using self-administered interviewer assisted method. LTPA was measured using Leisure Time Physical Activity Questionnaire designed specifically for Malaysian elderly with 2 section namely Exercise Physical Activity and Non-Exercise Physical Activity with 9 activities in total. Activity frequency measured with 5-point scale. Descriptive analysis conducted for all study variables and independent t-test, ANNOVA and multiple linear regression conducted for further analysis. Significant level was set at <0.05 p-value and 95% CI. 520 elderly patients with type 2 diabetes were included in this study with a response rate of 100%. Mean age of respondents were 67.99 ± 5.25 years (young-old 88.7%). Most respondents were male (57.7%), Indian (39.2%), married (70.4%), secondary school education level (43.3%). Mean household income was 3377.49 ± 4033.64 with 48.7% >Rm2001. Mean height 160.21 ± 9.70 cm and weight 68.70 ± 12.69 kg. Overall body mass index means 26.81 ± 4.72 with 43.3% overweight. Duration of diabetes 11.15 ± 9.11 years with 61.3 % ≤ 10 years. 78.1% has ≥3 co-morbidities and 66.2% had high knowledge on physical activity, mean score 24.69 ± 3.30. Attitude towards physical activity was positive, mean score 4.00 ± 0.44 and 68.7% respondents had good social network. Commonest resource available for physical activity was Park and 79% respondents had ≤ 2 resources. The LTPA was dominated by the Non-exercise physical activity (1.70 ± 1.16), with cleaning house – indoor as most frequently engaged non exercise physical activity. Meanwhile, commonest exercise based physical activity was walking, with mean score of 1.49 ± 1.70. Final linear regression model revealed, significant determinant for Leisure Time Physical Activity among elderlies with type 2 diabetes mellitus are age (B=-0.304, 95%CI: 0.426,0.746), gender (B=0.299, 95%CI: 0.207,0.392), education level (B=0.109, 95%CI: 0.012,0.205), ethnicity (Chinese - B=0.126, 95%CI: 0.009,0.243) and (Others - B= -0.402, 95%CI: - 0.760,0.045), presence of co-morbidities (B= -0.232, 95%CI: -0.338,- 0.127), vigorous exercise attitude (B= 0.115, 95%CI: 0.024,0.206) and social network (B= 0.202, 95%CI: 0.106,0.299). Majority of type 2 diabetes elderlies in Petaling district Selangor has low physical activity level with limited engagement in exercise based physical activity. Future planning and implementation of physical activity programs for T2DM elderlies should focus among those group of elderlies whom are old-old aged, male, lower education level, having >3 co-morbidities, living with poor social network and having negative attitude towards PA within vigorous exercise attitude.